Airflow vibration of diaphragmatic breathing: model and demonstration using optical biosensor - Toto Saktioto; Defrianto Defrianto; Nurfi Hikma; Yan Soerbakti; Syamsudhuha Syamsudhuha; Dedi Irawan; Okfalisa Okfalisa; Bambang Widiyatmoko; Dwi Hanto (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2023)
Optical fiber is increasingly popular and appreciated as a modern sensor technology in various sectors, one of which is for medical functions. This study was conducted to detect human diaphragmatic breathing flow using theoretical and experimental approaches. Initially, the lung model was formed using the finite element method and the Navier-Stokes equation by applying the principles of momentum and continuity. Furthermore, fiber Bragg grating (FBG) and single mode fiber (SMF) were experimentally designed with sinusoidal patterned macro-scale bending as a stretch sensor in a breathing belt applied to the diaphragm. The simulation model shows the airflow velocity increases up to 4 m/s when it flows into smaller branches. While the experimental results show that the largest power loss occurs at a buffer diameter of 0.8 cm. The power loss detected in SMF is a maximum of -0.18 dBm during inhalation and a minimum of -0.28 dBm during expiration. However, FBG bending is superior with high sensitivity.